PERCOBAAN PEMBUATAN PULP SULFAT DARI KAYU MAKADAMIA (MACADAMIA HILDEBRANDII VAN STEEN) - Rena M Siagian; Toga Silitonga (Jurnal Penelitian Hasil Hutan, 1988)
Macadamia hildebrandii  van Steen,  commonly   known  as makadamia,  belongs to the family  Proteaceae.   Until recently,   this  wood  has not  been  widely  used and only grown sporadically  in several places in Indonesia  mainly  used for non commercial  purposes.   The  wood  material  used  in the.  experiment was obtained  from  Sipangan Bolon,   North  Sumatra  for both  pulping   trials and  chemical  analyses.The  chemical  constituents   of  the  wood  are typically  of  those  tropical  wood  containing  46.6%  cellulose, 24.6% of lignin, and  relatively  low  14.4% pentosan. The average specific gravity  was 0.61 and the fibre length of  1.76 mm. The pulping  experiment was  conducted   in laboratory  digester employing 20% active alkali, 170°C  maximum temperature wich was maintained  for 120 minutes.  The cooking  sulfidity   was made at 2 levels i.e. 25%  and 30%.The makadamia pulp  yield  ranged from  32.4 to 34. 7% with  low Permangante  number  2.15   to 2. 64. The pulp  strength was fair and comparable  to those of the commercial  types.  By adding of anthraquinone   catalyst  at 0,1percent  by weight of the  wood  material  to cooking,   a  significant  improvement   in pulp  strength   was commenced. This is particular noticed when using 25% sulfidity  during the pulping.